ANALISIS PENGARUH RASIO PROFITABILITAS DAN SOLVABILITAS TERHADAP PERTUMBUHAN LABA (STUDI KASUS PADA PT TELEKOMUNIKASI INDONESIA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012 – 2017) - Natalia Dewi Prihatini; Loeky Rono Pradopo (Journal of Information System, Applied, Management, Accounting and Research, 2020)
The purpose of this study is to analyze how much influence the profitability ratio and solvency ratio simultaneously on the profit growth of PT Telekomunikasi Indonesia Tbk in the period 2012-2017. The research variables are profitability (X1), solvency (X2), and profit growth (Y). The type of research used is descriptive and explanatory research. While the type of research based on the nature of the data is quantitative research. The population of this study is the financial statements of PT Telekomunikasi Indonesia Tbk, while the sample is profit growth in 2012 - 2017 so the number of samples is 6 items. The sampling technique used was purposive sampling, namely sampling based on certain objectives. The results showed partially that there was an effect of profitability ratios on proven earnings growth with the value of t count test> t table or 2,781> 2,776. Then there is the effect of solvency ratio on earnings growth as evidenced by the value of t count> t table or 3.205> 2.776. Besides that, simultaneously there are effects of profitability and solvency ratios on profit growth. This is evidenced by the F test, the value of F count> F table or 11,195> 9.55 means that there is a significant effect and the coefficient of determination is 77.50%, which means that 77.50% contributes Profitability and Solvability simultaneously (together) to Profit Growth, while the remaining 22.50% is the influence of other factors. Based on this, it is suggested for further research, can add independent variables and add samples and years of the company that have not been taken from previous research. So that it can explain better profit growth.